Cadherin-11 Overexpression Induces Extracellular Matrix Remodeling and Calcification in Mature Aortic Valves. Issue 8 (August 2016) - Sung, Derek C.; Bowen, Caitlin J.; Vaidya, Kiran A.; Zhou, Jingjing; Chapurin, Nikita; Recknagel, Andrew; Zhou, Bin; Chen, Jonathan; Kotlikoff, Michael; Butcher, Jonathan T.
Abstract : Objective—: Calcific aortic valve (AoV) disease is a significant clinical problem for which the regulatory mechanisms are poorly understood. Enhanced cell–cell adhesion is a common mechanism of cellular aggregation, but its role in calcific lesion formation is not known. Cadherin-11 (Cad-11) has been associated with lesion formation in vitro, but its function during adult valve homeostasis and pathogenesis is not known. This study aims to elucidate the specific functions of Cad-11 and its downstream targets, RhoA and Sox9, in extracellular matrix remodeling and AoV calcification. Approach and Results—: We conditionally overexpressed Cad-11 in murine heart valves using a novel double-transgenic Nfatc1 Cre ;R26-Cad11 TglTg mouse model. These mice developed hemodynamically significant aortic stenosis with prominent calcific lesions in the AoV leaflets. Cad-11 overexpression upregulated downstream targets, RhoA and Sox9, in the valve interstitial cells, causing calcification and extensive pathogenic extracellular matrix remodeling. AoV interstitial cells overexpressing Cad-11 in an osteogenic environment in vitro rapidly form calcific nodules analogous to in vivo lesions. Molecular analyses revealed upregulation of osteoblastic and myofibroblastic markers. Treatment with a Rho-associated protein kinase inhibitor attenuated nodule formation, further supporting that Cad-11–driven calcification acts through the small GTPase RhoA/Rho-associated protein kinase signaling pathway. Conclusions—: This study identifies one of the underlying molecular mechanisms of heart valve calcification and demonstrates that overexpression of Cad-11 upregulates RhoA and Sox9 to induce calcification and extracellular matrix remodeling in adult AoV pathogenesis. The findings provide a potential molecular target for clinical treatment. Abstract : Supplemental Digital Content is available in the text.